Styrylpyridinium Derivatives for Fluorescent Cell Imaging - Reinis Putralis; Ksenija Korotkaja; Martins Kaukulis; Zhanna Rudevica; Juris Jansons; Olga Nilova; Martins Rucins; Laura Krasnova; Ilona Domracheva; Mara Plotniece; Karlis Pajuste; Arkadij Sobolev; et al. (MDPI AG, 2023)
A set of styrylpyridinium (SP) compounds was synthesised in order to study their spectroscopic and cell labelling properties. The compounds comprised different electron donating parts (julolidine, p-dimethylaminophenyl, p-methoxyphenyl, 3,4,5-trimethoxyphenyl), conjugated linkers (vinyl, divinyl), and an electron-withdrawing N-alkylpyridinium part. Geminal or bis-compounds incorporating two styrylpyridinium (bis-SP) moieties at the 1,3-trimethylene unit were synthesised. Compounds comprising a divinyl linker and powerful electron-donating julolidine donor parts possessed intensive fluorescence in the near-infrared region (maximum at ~760 nm). The compounds had rather high cytotoxicity towards the cancerous cell lines HT-1080 and MH-22A; at the same time, basal cytotoxicity towards the NIH3T3 fibroblast cell line ranged from toxic to harmful. SP compound 6e had IC50 values of 1.0 ± 0.03 µg/mL to the cell line HT-1080 and 0.4 µg/mL to MH-22A; however, the basal toxicity LD50 was 477 mg/kg (harmful). The compounds showed large Stokes' shifts, including 195 nm for 6a,b, 240 nm for 6e, and 325 and 352 nm for 6d and 6c, respectively. The highest photoluminescence quantum yield (PLQY) values were observed for 6a,b, which were 15.1 and 12.2%, respectively. The PLQY values for the SP derivatives 6d,e (those with a julolidinyl moiety) were 0.5 and 0.7%, respectively. Cell staining with compound 6e revealed a strong fluorescent signal localised in the cell cytoplasm, whereas the cell nuclei were not stained. SP compound 6e possessed self-assembling properties and formed liposomes with an average diameter of 118 nm. The obtained novel data on near-infrared fluorescent probes could be useful for the development of biocompatible dyes for biomedical applications.